2015
DOI: 10.1371/journal.pone.0142664
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) Attenuates Kidney Injury Due to Obstructive Nephropathy in Rats

Abstract: BackgroundAngiotensin-(1–7) [Ang-(1–7)] counteracts many actions of the renin-angiotensin-aldosterone system. Despite its renoprotective effects, extensive controversy exists regarding the role of Ang-(1–7) in obstructive nephropathy, which is characterized by renal tubulointerstitial fibrosis and apoptosis.MethodsTo examine the effects of Ang-(1–7) in unilateral ureteral obstruction (UUO), male Sprague-Dawley rats were divided into three groups: control, UUO, and Ang-(1–7)-treated UUO rats. Ang-(1–7) was cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
4
31
0
1
Order By: Relevance
“…Phosphorylated histone H3 is indicative of chromosome condensation during both mitosis and meiosis (manufacturer's information). We observed clear nuclear expression of PHH3 and our staining was consistent with previous reports using this antibody across species including: planaria (Sikes & Newmark, ); zebrafish (Yokokura et al, ) and rats (Kim et al, ).…”
Section: Methodssupporting
confidence: 92%
“…Phosphorylated histone H3 is indicative of chromosome condensation during both mitosis and meiosis (manufacturer's information). We observed clear nuclear expression of PHH3 and our staining was consistent with previous reports using this antibody across species including: planaria (Sikes & Newmark, ); zebrafish (Yokokura et al, ) and rats (Kim et al, ).…”
Section: Methodssupporting
confidence: 92%
“…Because we focused on histological and molecular changes of UUO kidney, we initially did not check the biochemical data such as BUN and serum creatinine level. However, many previous studies have reported that BUN and serum creatinine level was not significantly affected by only ipsilateral UUO due to the presence of a contralateral kidney with good renal function434445464748. Practically, we confirmed normal morphology and histology of contralateral kidney.…”
Section: Discussionsupporting
confidence: 79%
“…and xylazine (5 mg/kg, i.p.) as previous described [Kim et al., ]. Control rats were opened an abdominal cavity, but no ligature was made.…”
Section: Methodsmentioning
confidence: 99%